Assessing the Impact of Fruit Tree-Based Agroforestry, Parkland Agroforestry, and Boundary Planting on Soil Fertility and Carbon Stock in Erer District, Ethiopia - Sima Daba Bogale; Shemelis Abebaw (Journal of Landscape Ecology, 2025)
Soil degradation driven by deforestation and intensive agriculture has significantly reduced agricultural productivity and ecosystem services in Ethiopia’s dryland regions, particularly in the Erer District. This study evaluated the effectiveness of three agroforestry systems fruit tree-based agroforestry, parkland agroforestry, and boundary planting compared to conventional agriculture in enhancing soil fertility and soil organic carbon (SOC) stocks. A systematic plot design was implemented using 16 plots, each measuring 20 × 20 meters, with treatments randomly assigned to ensure representative sampling across the district. Within each plot, composite soil samples were collected at three depths (0–20 cm, 20–40 cm, and 40–60 cm) to capture vertical variations in soil properties. Key soil properties, including total nitrogen, available phosphorus, and potassium, were analyzed using standard laboratory methods, while SOC was estimated following established protocols. Additionally, above- and below-ground biomass were quantified using generalized allometric equations adapted to the local context. Results indicated that fruit tree-based agroforestry significantly increased nutrient availability and SOC, especially in the topsoil, and registered the highest above-ground biomass, suggesting a superior capacity for carbon sequestration and soil health improvement. Parkland agroforestry also enhanced soil fertility and SOC, albeit to a moderate degree, with its diverse species composition contributing to more stable nutrient cycling and moisture retention. In contrast, boundary planting, while showing the smallest gains in nutrient and SOC levels, was particularly effective in reducing soil erosion and improving localized water conservation, thus supporting overall soil quality. Collectively, these findings suggest that tailored agroforestry practices, especially fruit tree-based systems, can be sustainable strategies for restoring degraded soils, mitigating climate change, and boosting agricultural productivity in dryland areas. This study provides critical insights for policymakers and land managers seeking to implement agroforestry interventions for long-term environmental conservation and sustainable land use in the Erer District.